Activation of α7 nicotinic acetylcholine receptor alleviates Aβ1-42-induced neurotoxicity via downregulation of p38 and JNK MAPK signaling pathways. (November 2018) - Chang, Ke-Wei; Zong, Hang-Fan; Ma, Kai-Ge; Zhai, Wan-Ying; Yang, Wei-Na; Hu, Xiao-Dan; Xu, Jie-Hua; Chen, Xin-Lin; Ji, Sheng-Feng; Qian, Yi-Hua
Abstract: Amyloid β peptide 1–42 (Aβ1-42 ) could induce cognitive deficits through oxidative stress, inflammation, and neuron death in Alzheimer's disease (AD). MAPK pathways have been thought to mediate Aβ1-42 -induced neuroinflammation responses, neuron death and cognitive decline in AD. The α7 nicotinic acetylcholine receptor (α7nAChR) exerts a neuroprotective effect. However, whether α7nAChR alleviates Aβ1-42 -induced neurotoxicity through MAPKs (p38, ERK, JNK) in vivo remains unclear. In our study, memory was assessed in C57BL/6 mice using a Y-maze test. Cell death was assessed by Nissl and Hoechst staining and Bax, Bcl-2, Caspase 3, and Cytochrome C levels using Western blotting. Oxidative stress was assayed by superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA) levels. Inflammation was examined with GFAP and Iba1 using immunohistochemistry. The Aβ degrading enzymes insulin degrading enzyme (IDE) and neprilysin (NEP) were tested using Western blotting. We found that activating α7nAChR or inhibiting p38 or JNK pathway alleviated Aβ1-42 -induced cognitive deficits and neuron loss and death by reducing oxidative stress. In addition, activating α7nAChR or inhibiting p38 or JNK pathway also reduced inflammation, which was observed as reduced GFAP and Iba1 levels with different effects on Aβ degrading enzymes. Finally, we found that the activation of α7nAChR led to the downregulation of pp38 and pJNK levels. Conversely, the inhibition of p38 or JNK resulted in the upregulation of α7nAChR levels in the hippocampus and cortex. Our data indicate that the activation of α7nAChR alleviates Aβ1-42 -induced neurotoxicity, and this protective effect might act through the downregulation of p38 and JNK MAPKs. Highlights: Activation of α7nAChR mitigates Aβ-induced cognitive deficits via p38 and JNK MAPKs. Activation of α7nAChR prevents cell death, oxidative stress and neuroinflammation. Activation of α7nAChR reduces the levels of insulin degrading enzyme and neprilysin.